Phylogenetic relationships and systematics of tapeworms of the family Davaineidae (Cestoda, Cyclophyllidea), with emphasis on species in rodents - Haukisalmi, Voitto; Ribas, Alexis; Hugot, Jean-Pierre; Morand, Serge; Chaisiri, Kittipong; Junker, Kerstin; Matthee, Sonja; Spickett, Andrea; Lehtonen, Jukka T; Feliu, Carlos; Henttonen, Heikki (Folia parasitologica, 2024)
The present study aims at clarifying the poorly known phylogenetic relationships and systematics of cestodes of the family Davaineidae Braun, 1900 (Cyclophyllidea), primarily the genus Raillietina Fuhrmann, 1920 and of the subfamily Inermicapsiferinae (Anoplocephalidae) from mammals (mostly rodents, 31 new isolates) and birds (eight new isolates). Phylogenetic analyses are based on sequences of the large subunit ribosomal RNA gene (28S) and mitochondrial NADH dehydrogenase subunit 1 gene (nad1). The main phylogenetic pattern emerging from the present analysis is the presence of three independent lineages within the main clade of the subfamily Davaineinae, one of which is almost entirely confined to species from rodents and the other two show a mixture of species from birds and mammals. It is suggested that the major diversification of the main clade took place in birds, possibly in galliforms. The subsequent diversification included repeated host shifts from birds to mammals and to other birds, and from rodents to other mammals, showing that colonisation of new host lineages has been the main driver in the diversification of davaineine cestodes. It is also shown that all isolates of Inermicapsifer Janicki, 1910, mainly from rodents, form a monophyletic group positioned among Raillietina spp. in the "rodent lineage", indicating that the genus Inermicapsifer is a member of the family Davaineidae. This means that the subfamily Inermicapsiferinae and the family Inermicapsiferidae should be treated as synonyms of the Davaineidae, specifically the subfamily Davaineinae. Three additional genera generally included in the Inermicapsiferinae, i.e. Metacapsifer Spasskii, 1951, Pericapsifer Spasskii, 1951 and Thysanotaenia Beddard, 1911, are also assigned here to the Davaineidae (subfamily Davaineinae). Raillietina spp. were present in all three main lineages and appeared as multiple independent sublineages from bird and mammalian hosts, verifying the non-monophyly of the genus Raillietina and suggesting a presence of multiple new species and genera.
Keywords: 28S; nad1; cestodózy; Inermicapsiferinae; Birds; Inermicapsifer; Raillietina; Animals; RNA ribozomální 28S; zvířata; Rodentia; hlodavci; Davaineinae; fylogeneze; Cestoda; NADH-dehydrogenasa; NADH Dehydrogenase; phylogeny; ptáci; Cestode Infections; Phylogeny; RNA, Ribosomal, 28S; Anoplocephalidae